PENGEMBANGAN MANAJEMEN DAKWAH JAMA'AH TABLIGH DALAM MEMBINA MASYARAKAT ISLAM SUKU TERASING - Ibrahim Latepo; Suharto Suharto (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2015)
This paper deals with the development of Jama'ah Tabligh's da'wah management in guiding Muslim community from isolated ethnic group in Subdistrict of Palasa, District of Parigi- Moutong. This study used an analysis of a science of da'wah. Jama'ah Tabligh's management of da'wah refers to modern management that includes planning, organizing, controlling and evaluating. From this concept, the principles of management are developed which include forecasting, planning, organizing, decision making, actuating, communicating, coordinating, centralization, motivating, controlling, budgeting, evaluatingand reporting, and so on. This becomes a reference, and will be developed into elements of da'wah conducted by Jama'ah Tabligh. These elements are developed into the model of travelling for the sake of Allah (khuruj fi sabilillah), which include activity at the site ('amal maqami) and moving activity ('amal intiqali). Both activities are made as a model for guiding both individuals and societ.